Zaznavanje potresne ogroženosti pri strokovnjakih in nestrokovnjakih - Fajfar, Peter (Gradbeni vestnik, 2014)
The results of a survey on perception of earthquake risk in general and risk to different types of constructions in particular, which was carried out on a sample of 240 engineers and 502 lay persons, are presented. In the introduction, some general findings about people%s coping with earthquakes and their consequences are given. The results of the survey show that lay people feel less worried because of earthquake threat to Slovenia than experts. Regarding the perception of seismic risk to different types of buildings, for experts both the time period and the type of construction are important, as expected.
Keywords: earthquake; endangerment; ogroženost; potres; risk; threat perception; tveganje; type of construction; vrsta gradnje; zaznava ogroženosti